How New Zealand greyhound racing industry licensed persons perceive the industry, greyhound welfare, and their ability to create change : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Animal Science at Massey University, Manawatu, New Zealand - Korver, Sandrine (Massey University, 2024)
The greyhound racing industry in New Zealand is facing increasing concerns about animal welfare, and its social license to operate is diminishing. A social license to operate refers to the informal and intangible agreement that determines whether an industry or business can continue operating based on its social acceptability. The New Zealand government, represented by Hon. Grant Robertson, put the greyhound racing industry on notice in September 2021 following an independent review of the industry and its practices. The review recommended major changes in three areas: data recording, transparency of all activities, and improvement of animal welfare in general. In this study, I aimed to better understand greyhound racing industry participants' perspectives, practices, and attitudes, particularly regarding greyhound welfare and management. This study provided critical insight into a commonly overlooked and unvalued stakeholder whose perspectives are essential in understanding the appetite to make changes to align with evolving community expectations. I surveyed 46 New Zealand registered greyhound racing license holders and collected quantitative and qualitative data. I used a mixed-methods approach, including reflexive thematic analysis for qualitative data. This research provides a deeper understanding of the diverse perspectives, motivations, and opinions of license holders within the New Zealand greyhound racing industry. The participants care deeply about their dogs and understand the basic requirements for the racing greyhounds. However, they could benefit from further education regarding what good welfare means for greyhounds. The participants rated affective state and survival-related categories of welfare as the most important categories for ensuring good greyhound welfare. Behaviour interactions were rated as less important towards maintaining good greyhound welfare. Their responses around greyhound welfare indicated further clarification of terminology would be beneficial and would elucidate whether increased animal welfare educational efforts are necessary. This research highlights the key areas where changes are needed and suggests effective approaches to support, involve, empower, and educate the racing greyhound license holders. Greyhound license holders felt excluded from decision-making that impacts them and their dogs. They wanted greater support from industry authorities to improve canine welfare. They expressed their eagerness to improve their industry and their desire to be included in decisions regarding changes, through being included in committees, meetings and ensuring their input is acknowledged and applied. They are committed to improving the social license to operate. They want the public to understand the sport better and greyhound welfare through increased transparency and openness, by involving the public in open days and events. The findings of the study will help the license holders adapt and apply these approaches to improve greyhound welfare and management practices.
Keywords: 300306 Animal welfare